Pakistan : can the United States secure an insecure state? - Fair, C. Christine (Rand Corporation monograph series ;, 2010)
Describing Pakistan's likely future course, this book seeks to inform U.S. efforts to achieve an effective foreign policy strategy toward the country. The book forms an empirical analysis of developments in Pakistan and an assessment of the effectiveness of U.S. policy as of August 2009. Drawing on interviews of elites, polling data, and statistical data on Pakistan's armed forces, the book presents a political and political-military analysis. Primary data and analyses from Pakistanis and international economic organizations are used in the book's demographic and economic analyses. The book assesses Pakistan's own policies, based on similar sources, on government documents, and on the authors' close reading of the assessments of several outside observers. The book also discusses U.S. policy regarding Pakistan, which was based on interviews with U.S. policymakers and on U.S. policy documents. The policy recommendations are based on an assessment of the findings in all these areas. The book concludes with a number of recommendations for the U.S. government and the U.S. Air Force concerning how the United States could forge a broad yet effective relationship with this complicated state. --Publisher description.